Kerjasama Orang Tua, Sekolah, dan Pemerintah dalam Upaya Pencegahan Penyalahgunaan Narkoba pada Remaja - Al Ansari, Muhammad; Amirullah, Amirullah; Ruslan, Ruslan (Universitas Negeri Malang, 2020)
This study aimed to determine the mode of drug distribution in society, the form of cooperation between parents, schools, and the government in preventing drugs in adolescents, and the obstacles faced in preventing drugs. This study used a descriptive qualitative method. The mode used by drug traffickers was to wrap drugs in food/beverage packages that are transported on the deck of the ship and put them in a modified vehicle tank. The form of cooperation between parents, schools, and the sub-district was a joint-venture. The obstacles faced in preventing drug abuse or spread among adolescents are the lack of public understanding of drug prevention, the large negative influence of peer groups, the lack of school facilities and infrastructure, and many apathetic people.